Recurso especial: a extensão de seus efeitos e a atuação do Superior Tribunal de Justiça no caso concreto - Brazil, Renato Caldeira Grava (2018)
The role of the Superior Court of Justice is of undoubted importance in the Brazilian judicial structure, particularly in relation to standardizing Brazilian case law and providing guidance to the lower courts in the form of precedents. However, the Court's pronouncements do not always, in practice, lead to the desired legal security. In the light of that reality, this study examines the history behind the establishment of the Superior Court of Justice and the introduction of the so-called "Special Appeal" (recurso especial), analyzing the formalities inherent to this form of appeal (including the stringent prerequisites to admissibility) and the peculiarities of the manner in which the appeals are tried before the court. These aspects of the Special Appeal have given rise to considerable debate. Some of of the practical ramifications of these aspects are addressed in this study. The author examines the manner in which the admissibility of Special Appeals is decided upon and the means of challenging a denial of leave to proceed. In relation to the merits of the case, the study considers the effects of lodging a Special Appeal, in particular the scope of the examination by the Court (the efeito devolutivo) and the extent to which the court can draw on extraneous matters such as public policy issues (the efeito translativo). These are, in effect the two aspects that delimit the role of the Superior Court. We then examine in detail the way in which the Superior Court has dealt with the issues submitted to it, in terms of form (the orders made), time (and timing) and the limits of intervention of the Court in its rulings on Special Appeals